Laparoscopic right hemicolectomy for rare case of caecal duplication cyst manifested as intussusception in an adult: a case report - Shetty, Tarun; Chavan, Kamini (International Surgery Journal, 2022)
Duplications of the alimentary tract are very rare congenital anomalies, and of which two thirds of cases manifest before the age of two years. Among duplication of alimentary tract colonic duplications are unusual, they may remain asymptomatic and present in adulthood. This report discussed a case of a 26-year-old female who presented with abdominal pain due to colocolic intussusception. Right hemicolectomy was performed for same and the diagnosis of a caecal enterogenous cyst was confirmed by histopathological exam. This report implied that although alimentary tract duplications are rare, they should be considered in any case presenting with abdominal pain. Laparoscopic right hemicolectomy can be performed for good cosmetic results, less morbidity and early recovery.